Malassezia overgrowth in dogs in northern Italy: frequency, body distribution, clinical signs and effects of pharmacologic treatments - Michele Berlanda; Carlotta Valente; Carlo Guglielmini; Patrizia Danesi; Barbara Contiero; Helen Poser (Veterinaria Italiana, 2022)
The present study describes Malassezia populations in clinically healthy dogs (HD) and dogs with Malassezia overgrowth (MO), and evaluates the correlation with clinical signs and previous treatments. Thirteen clinically HD and 84 dogs with MO were enrolled. Clinical history and previous treatments were recorded. After a complete physical and dermatological examination, Canine Atopic Dermatitis Extent and Severity Index_03 scores were calculated. Samples for cytology and mycological cultures were obtained from four body regions and from skin lesions. Malassezia overgrowth was diagnosed by cytology. A global score (GS) for quantitative evaluation of the population of Malassezia was calculated. In dogs with MO, the highest frequency of yeast detection was found in skin lesions (82%, P < 0.001). Sum of GS (GSs) obtained from dogs with MO (68, 0‑621) was significantly higher compared to those of HD (3, 0‑48, P < 0.001). GSs in dogs previously treated with antibiotics (312.5, 30‑975) was significantly higher compared to those of dogs that not have received antibiotics (80, 0‑975, P = 0.015). No difference was found between dogs treated and those not treated with steroids.